Doctoral education in international context : connecting local, regional and global perspectives - Mallan, Vijay Kumar (Universiti Putra Malaysia Press, 2011)
As the doctorate becomes increasingly international, communities of educators, researchers and policy makers are being formed who can consider the international trends, patterns and issues facing universities, supervisors and students in these changing times. Doctoral education in international context was produced in the context of the 2nd International Doctoral Education Research Network (IDERN) conference in Malaysia. It is addressed directly to doctoral supervisors, students, doctoral program coordinators and policy makers and discusses many key issues arising in the changing doctoral education landscape. It provides useful theoretical underpinnings and insights into the complexity of contemporary global doctoral education and how these issues are negotiated across boundaries.